2015
DOI: 10.1177/0885328215575763
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral microcrystals encapsulating bone morphogenetic protein 2 improve healing in the alveolar ridge

Abstract: Atelocollagen sponges incorporating polyhedra encapsulating bone morphogenetic protein 2 (BMP-2) were implanted into lateral bone defects in the mandible. Half of the bone defects on the left side were treated with atelocollagen sponges containing 1.8 × 10(7) BMP-2 polyhedra, and half were treated with sponges containing 3.6 × 10(6) BMP-2 polyhedra. As controls, we treated the right-side bone defects in each animal with an atelocollagen sponge containing 5 µg of recombinant human BMP-2 (rhBMP-2) or 1.8 × 10(7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…This work builds on previous data where pBMP-2 incorporated into an absorbable collagen sponge (ACS) promoted bone formation to repair a critical-sized defect in a rat calvaria model, with superior efficacy to conventional rBMP-2 [ 26 ]. Furthermore, incorporation of pBMP-2 into an atelocollagen sponge facilitated the regeneration of new bone in the mandibular alveolar bone ridge [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This work builds on previous data where pBMP-2 incorporated into an absorbable collagen sponge (ACS) promoted bone formation to repair a critical-sized defect in a rat calvaria model, with superior efficacy to conventional rBMP-2 [ 26 ]. Furthermore, incorporation of pBMP-2 into an atelocollagen sponge facilitated the regeneration of new bone in the mandibular alveolar bone ridge [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absorbable collagen sponges or atelocollagen sponges, both of which incorporated polyhedron-encapsulated bone morphogenetic protein-2, have been shown to be effective for the complete and rapid healing of critically sized bone defects in mammals, highlighting the effectiveness of combining polyhedronencapsulated cytokines with biocompatible 3D substitutes to fabricate extracellular matrices that can control in vivo cell activities (26,28,29). However, scaffolds containing mammal-derived components, such as collagen or coagulation factor XIII, may present risks when used in human bodies because they could be contaminated by prions or viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the activity of cytokines encapsulated in polyhedra, which are protein microcrystals of cypovirus, can be stably maintained over long periods in both ex vivo and in vivo environments, and can be slowly released to stimulate the growth and differentiation of many cell types continually (14,(24)(25)(26)(27)(28)(29). Therefore, to determine whether sericin hydrogels can act as scaffolds to support cell growth and differentiation, we cultivated the mouse embryonic stem (ES) cell line EB5 on sericin hydrogels that were overlaid with a medium containing canonical recombinant human leukemia inhibitory factor (rhLIF) or that incorporated polyhedron-encapsulated LIF (24) (SI Appendix, SI Materials and Methods).…”
Section: Expression and Physiological Effects Of Truncated P1a In Silmentioning
confidence: 99%
“…Collectively, our data suggest that DC‐STAMP, together with MMP‐2 and MMP‐9 (Galliera et al, ; Rocha et al, ), can be a useful tool for monitoring, in parallel with other bone turnover markers, to evaluate bone remodeling and tissue healing. Given that DC‐STAMP+ cells are homing to bone fracture sites, a step forward approach is to molecular engineer a chimeric DC‐STAMP protein by which DC‐STAMP is able to bring small peptides/proteins such as bone morphogenetic protein 2 (BMP‐2) or MMP‐9 (Kim et al, ; Matsumoto et al, ; Miller et al, ; Saito et al, ; Wang et al, ) with healing‐promoting effects to bone fracture sites.…”
Section: Clinical Potentials Of Dc‐stampmentioning
confidence: 99%